Effect of stage of maturity at harvest for forage pea (Pisum sativum L.) on eating behavior, ruminal fermentation, and digestibility when fed as hay to yearling beef heifers - Pursley, Alex A (Transl Anim Sci, 2019)
The objective of this study was to evaluate the stage of maturity at harvest for pea hay (Pisum sativum L., c.v. CDC Horizon) on dry matter intake (DMI), eating behavior, ruminal fermentation, and digestibility when fed to beef heifers. Pea hay was cut at EARLY (defined to occur when flat pods were on one or more nodes), MID (when seeds filled the pods at one or more nodes and the leaves were changing from green to gold), and LATE (yellow dry seeds filled pods on most or all of the nodes and the pods and leaves had a yellow color) phases, and was cured in the field and baled. Six ruminally-cannulated Speckle Park heifers were used in a replicated 3 × 3 Latin square design with three 18-d periods including 12 d for adaptation, 2 d for measurement of ruminal pool sizes, and 4 d for the collection of eating behavior, ruminal pH, ruminal digesta, and feces. For all treatments, the respective pea hay was included at 40% of the dietary DM. Stage of maturity at harvest for pea hay did not affect total DMI, pea hay DMI, or the total short-chain fatty acid concentration in ruminal fluid with averages of 8.6 kg/d, 3.2 kg/d, and 96.55 mM, respectively. The duration of time spent ruminating decreased with advancing pea hay maturity when reported as min/d, min/kg DMI, and min/kg neutral detergent fiber (NDF) (P ≤ 0.01). Mean ruminal pH also decreased with advancing pea maturity (P < 0.01). The ruminal DM and undigested NDF corrected for OM pools were not affected by stage of maturity (P ≥ 0.55) nor was the rate of digestion for NDF. However, NDF passage rate decreased by 0.21%/h with advancing pea hay maturity (P = 0.02). Apparent total tract digestibility of NDF (average = 16.30%, P = 0.41) was not affected, but starch digestibility decreased from 96.10% to 93.08% with advancing pea hay maturity (P = 0.07). Overall, stage of maturity at harvest for pea hay does not appear to affect DMI or NDF digestibililty but decreases chewing activity, apparent total tract starch digestibility, ruminal pH, and ruminal NDF passage rate.